Die Dramatische Zeit in Senecas Tragodien - Heil, Andreas, 1969- (Mnemosyne, Supplements, 2013)
In four separate studies, Andreas Heil shows that Seneca, in his tragedies Thyestes , Hercules furens , Troas ( Troades ) and Medea , handles dramatic time less experimentally than has been assumed before. In all of these plays, taking into consideration the accompanying action on the stage and the characters' respective points of view, a gradually developing plot can be reconstructed. Thus, the survey considerably deepens our understanding of Seneca's dramatic technique. In vier Einzelstudien zeigt Andreas Heil, daß Seneca mit der dramatischen Zeit in seinen Tragödien Thyestes , Hercules furens , Troas ( Troades ) und Medea weniger experimentell verfährt, als bislang angenommen wurde. In allen untersuchten Stücken läßt sich - berücksichtigt man die begleitende Bühnenhandlung und die jeweilige Figurenperspektive - eine sukzessive sich entwickelnde Handlung rekonstruieren. Die Untersuchung leistet somit einen wichtigen Beitrag zum besseren Verständnis der dramatischen Technik Senecas.